2017
DOI: 10.1016/j.marpolbul.2016.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Shipping noise in a dynamic sea: a case study of grey seals in the Celtic Sea

Abstract: Shipping noise is a threat to marine wildlife. Grey seals are benthic foragers, and thus experience acoustic noise throughout the water column, which makes them a good model species for a case study of the potential impacts of shipping noise. We used ship track data from the Celtic Sea, seal track data and a coupled ocean-acoustic modelling system to assess the noise exposure of grey seals along their tracks. It was found that the animals experience step changes in sound levels up to~20dB at a frequency of 125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Seismic air-guns 240-250 dB re 1 μPa Richardson et al, 1995 Seismic air-guns 195-210 dB re 1 μPa Wardle et al, 2001 Seismic air-guns 186-191 dB re 1 μPa Skalsky et al, 1992 Drill vessel 174-185 dB re 1 μPa Richardson et al, 1995 Ship noise (dynamic sea conditions) 173-185 dB re 1 μPa Chen et al, 2017 Piling noise 164 dB re 1 μPa Spiga et al, 2017 Small or medium size vessels (ferry & motorboat) 150-180 dB re 1 μPa Richardson et al, 1995 Ship noise (engine exhausts, in port) 135-142 dB re 1 μPa EPA, 2010…”
Section: Review Article Rmentioning
confidence: 99%
“…Seismic air-guns 240-250 dB re 1 μPa Richardson et al, 1995 Seismic air-guns 195-210 dB re 1 μPa Wardle et al, 2001 Seismic air-guns 186-191 dB re 1 μPa Skalsky et al, 1992 Drill vessel 174-185 dB re 1 μPa Richardson et al, 1995 Ship noise (dynamic sea conditions) 173-185 dB re 1 μPa Chen et al, 2017 Piling noise 164 dB re 1 μPa Spiga et al, 2017 Small or medium size vessels (ferry & motorboat) 150-180 dB re 1 μPa Richardson et al, 1995 Ship noise (engine exhausts, in port) 135-142 dB re 1 μPa EPA, 2010…”
Section: Review Article Rmentioning
confidence: 99%
“…), but there is little published information using at‐sea movements of seals in relation to vessel activity (Chen et al . ). Several studies have called for monitoring of areas where there is high incidence of shipping traffic (Merchant et al .…”
Section: Introductionmentioning
confidence: 97%
“…This is because of the dipole radiation pattern of a ship and its image source, yielding a propagation loss well above the wrongly, yet commonly applied 20 log 10 (range) at shallow inclination angles (e.g., Ainslie et al, 2014). Using sound propagation models, Chen et al (2017) showed that gray seals experienced step changes of up to 20 dB in the received ship noise levels as they dove throughout the water column in the Celtic Sea. This was because of environmental features such as thermoclines, which a geometric propagation loss model cannot account for.…”
Section: Common Issues and Problemsmentioning
confidence: 99%